WHEELS OF JUSTICE: ANALYSING THE LEGAL STATUS OF AUTONOMOUS VEHICLES IN CONTEMPORARY LEGAL REALM - Rai, Smriti; Chauhan, Deepak Kumar; Kumawat, Dharmendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The research paper examines the complex legal issue of determining the status of autonomous vehicles (AVs) as an independent legal entity or an agent of the manufacturer. The paper delves into the concept of legal personhood and its application to artificial intelligence (AI) systems, including AVs. It explores various theories of legal personhood, such as the Natural Law Theory, Will Theory, and Function-based Theories, and their relevance to the classification of AVs. The paper also discusses the theory of agency law and its potential implications for the relationship between AVs and their manufacturers or developers. The paper analyzes the current Indian legal framework, including the Motor Vehicles Act and the Consumer Protection Act, and their limitations in addressing the legal issues posed by AVs. It highlights the ambiguity in liability determination, particularly in the case of partially automated vehicles, where the role of the human driver and the AV’s decision-making process must be carefully considered. The paper proposes a hybrid approach to the legal status of AVs, combining elements of both independent legal personhood and agency of the manufacturer. The paper emphasizes the need for comprehensive and adaptable legislation to address the evolving landscape of autonomous vehicle technology and ensure the safety and accountability of these systems. It acknowledges the complex and rapidly changing nature of automated vehicle technology and calls for further research and discussion to develop a robust legal framework that can effectively govern the integration of AVs into India’s transportation ecosystem.